Facultative sex ratio adjustment in natural populations of wasps: cues of local mate competition and the precision of adaptation. - Burton-Chellew, M; Koevoets, T; Grillenberger, B; Sykes, E; Underwood, S; Bijlsma, K; Gadau, J; van de Zande, L; Beukeboom, L; West, SA; Shuker, D (2008)
Sex ratio theory offers excellent opportunities to examine the extent to which individuals adaptively adjust their behavior in response to local conditions. Hamilton's theory of local mate competition, which predicts female-biased sex ratios in structured populations, has been extended in numerous directions to predict individual behavior in response to factors such as relative fecundity, time of oviposition, and relatedness between cofoundresses and between mates. These extended models assume that foundresses use different sources of information, and they have generally been untested or have only been tested in the laboratory. We use microsatellite markers to describe the wild oviposition behavior of individual foundresses in natural populations of the parasitoid wasp Nasonia vitripennis, and we use the data collected to test these various models. The offspring sex ratio produced by a foundress on a particular host reflected the number of eggs that were laid on that host relative to the number of eggs that were laid on that host by other foundresses. In contrast, the offspring sex ratio was not directly influenced by other potentially important factors, such as the number of foundresses laying eggs on that patch, relative fecundity at the patch level, or relatedness to either a mate or other foundresses on the patch.